Comparing robot-assisted vs. laparoscopic proctectomy for rectal cancer surgical and oncological outcomes - Wang, Wenpeng; Liu, Jia; Wang, Jiefu; Huang, Jinghao; Wang, Junfeng (Frontiers in Surgery, 2025)
BackgroundRobotic-assisted proctectomy (RAP) is increasingly used for rectal cancer, but its long-term benefits over laparoscopic proctectomy (LP) remain debated. While RAP offers technical advantages, its clinical equivalence requires further validation, particularly in anatomically challenging cases.MethodsWe conducted a retrospective analysis of all eligible patients who underwent RAP or LP for rectal cancer at Tianjin Medical University Cancer Institute and Hospital between 2019 and 2024.ResultsIn the overall cohort, RAP demonstrated significantly longer operative times (246.69 vs. 174.53 min, p < 0.001), greater blood loss (109.77 vs. 57.58 ml, p < 0.001), and higher costs (117,030.88 vs. 81,054.16 yuan, p < 0.001) compared to LP, with only a marginally shorter postoperative stay (8.47 vs. 8.64 days, p < 0.05). In terms of postoperative complications, RAP showed a trend towards fewer overall Clavien-Dindo Grade ≥ III complications (1.2% vs. 6.6%) compared to LP, although this difference was not statistically significant (p = 0.064). There were no significant differences in disease-free survival (DFS) (p = 0.575) or overall survival (OS) (p = 0.619) between the two groups. For the subgroup analysis of rectal cancers ≤ 5 cm from the anus, RAP achieved superior surgical precision, with 100% negative circumferential resection margin (CRM) (vs. 87.1% in LP, p = 0.042) and 100% complete mesorectal integrity (vs. 83.9% in LP, p = 0.053), alongside faster functional recovery (time to first flatus: 3.47 vs. 3.90 days, p = 0.034; time to urination: 2.10 vs. 2.65 days, p = 0.007). Recurrence rates were lower with RAP (10% vs. 19.4%), though survival outcomes remained similar between RAP and LP (p = 0.253)ConclusionWhile RAP incurs longer operative times and higher costs, it demonstrates superior precision in anatomically complex cases, evidenced by improved CRM status and mesorectal preservation. Although survival outcomes remain comparable, RAP's advantages in functional recovery and potential recurrence reduction warrant further investigation.